2022
DOI: 10.7759/cureus.21359
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Etiology for a Chronic Subdural Hematoma: Whole-Body Vibration Machine

Abstract: A chronic subdural hematoma is more common in the elderly, particularly after a minor trauma sustained several weeks before the diagnosis. The use of a whole-body vibration machine had not been reported as an etiology. We report an 80-year-old male patient without a history of head or body trauma who developed a bilateral chronic subdural hematoma and required surgery to drain the hematoma. Four weeks before the diagnosis, he purchased and used a whole-body vibration machine. The first time he used the whole-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Orlando De Jesus et al reported the case of an 80-year-old patient who presented with an association of bilateral CSDH and suprasellar AC following the use of a Whole-Body Vibration Machine. He was immediately operated with bilateral burr holes at the frontal and parietal areas with total post operative recovery [20]. Regarding the treatment, there is no consensus in the management of CSDH associated with an AC.…”
Section: Discussionmentioning
confidence: 99%
“…Orlando De Jesus et al reported the case of an 80-year-old patient who presented with an association of bilateral CSDH and suprasellar AC following the use of a Whole-Body Vibration Machine. He was immediately operated with bilateral burr holes at the frontal and parietal areas with total post operative recovery [20]. Regarding the treatment, there is no consensus in the management of CSDH associated with an AC.…”
Section: Discussionmentioning
confidence: 99%